Teaching Literature Through the Intercultural Approach Meta-Analysis of Ahmed Mehdaoui’s Study: TOWARDS AN INTERCULTURAL APPROACH TO TEACHING CIVILISATION IN THE FOREIGN LANGUAGE CLASSROOM - HADJADJ, Noureddine; ATTIA, Saddam Hossin; CHERFAOUI, Samia (University of Ammar Theledji -Laghouat, 2020)
As we live in a globalized world where we frequently interact with people from different cultural background. Hence, the development of learners’ intercultural communication is inevitable. Literature is one of the best subjects at English as foreign language departments that offers students the ability to access the targeted community world in order to prepare them for potential cross-cultural communication in which they may encounter linguistic and cultural barriers. The aim of this research is to understand the extent of intercultural approach contributions within teaching literature in the departments of the Algerian English language by investigating the link between language and culture during literature lectures and indicate the obstacles and barriers that interrupt the implementation of intercultural approach to make learning-teaching process easier for the teacher and sufficient for the learner. To test the hypothesis which are; Language is a part of culture which confirms that culture of targeted language positively affects language acquisition, the application of intercultural approach by cultural analyze and critic art works, and the contribution of intercultural approach is to understand the updated English language. We relied on the data analysis of the students’ and the teachers’ questionnaire conducted by DR. Mehdaoui which is close enough to our thesis then we made our analysis to tackle our own research using these statistics. after that, we made a discussion about the results. The findings of research demonstrate many drawbacks concerning the students, teachers and the programme. The teachers lack of motivation and conferences that gives recommendations about intercultural approach. Furthermore, the students struggle with unexpected English that varies from what they watched in movies, music …etc. they found themselves in front of direct grammar instructions. Add to that the programme of literature that is fully charged (especially in the first year) with rules that could be learnt by time